Philosophy of Striving and Making a Living in Institutions of Traditional Studies - Badri, Khairul Nizam Zainal (Asatiza: Jurnal Pendidikan, 2022)
Institutions of traditional learning (pondok) are often considered as places to acquire the sciences of the hereafter. On the other hand, the statement seems to illustrate that the students brought up in the institution are not concerned with worldly matters. The learning curriculum is said not to care about the function of the mind but instead makes students passive and only follow what is presented by the teacher. Using a content analysis approach, this study pays attention to the content of the book Ta’alim Al-Muta’allim written by Imam Al-Zarnuji. This book is a guide for the citizens of traditional educational institutions whether in terms of curriculum, aspects of teaching and learning, and ethics of life. The main objective of this study is to see whether the use of the book can influence positive thinking and lifestyle that not only think about the question of the hereafter but also perform the responsibilities that need to be fulfilled in the world. The results of the study found that the content of the book not only focuses on educational practice, but also encourages students to earn a living but with good intentions, especially to increase knowledge. In other words, students are not taught to sideline worldly affairs but still need to be aware of worldly affairs but with a high awareness that every job must be based on the importance of worship and be able to meet the needs of the hereafter.